Penurunan Kadar FFA (Free Fatty Acid) Minyak Jelantah Menggunakan Adsorben Arang Aktif Ampas Tebu Pada Proses Pembuatan Biodiesel - Yuli Hananto; Juwita Rosdiana (Indonesian Journal Publisher, 2023)
One of the obstacles in utilizing used cooking oil as a raw material for making biodiesel is the high FFA (Free Fatty Acid) content. An alternative way that can be used to reduce FFA levels is to use adsorbents to adsorb free fatty acids. This study aims to use bagasse as an adsorbent for activated charcoal to reduce the FFA content of used cooking oil in the process of making biodiesel. The process of reducing the FFA of used cooking oil was carried out by an adsorption process using activated bagasse charcoal with an increased temperature of 100 oC to accelerate the rate of adsorption and evaporation of water trapped in the used cooking oil while stirring at 500 rpm with a magnetic stirrer. The most optimal adsorbent mass for bagasse activated charcoal is to use a mass of 15% w/v used cooking oil, because it has the lowest average FFA value compared to other masses. The most optimal adsorption time for used cooking oil is at 60 minutes of adsorption because it has the lowest average FFA value compared to other adsorption times. FAME.